Opposed regulation of corepressor CtBP by SUMOylation and PDZ binding - Lin, Xia; Sun, Baohua; Liang, Min; Liang, Yao-Yun; Gast, Andreas; Hildebrand, Jeffrey; Brunicardi, F. Charles; Melchior, Frauke; Feng, Xin-Hua (Molecular cell, 2003)
The transcription corepressor CtBP is often recruited to the target promoter via interaction with a conserved PxDLS motif in the interacting repressor. In this study, we demonstrate that CtBP1 was SUMOylated and that its SUMOylation profoundly affected its subcellular localization. SUMOylation occurred at a single Lys residue, Lys428, of CtBP1. CtBP2, a close homolog of CtBP1, lacked the SUMOylation site and was not modified by SUMO-1. Mutation of Lys428 into Arg (K428R) shifted CtBP1 from the nucleus to the cytoplasm, while it had little effect on its interaction with the PxDLS motif. Consistent with a change in localization, the K428R mutation abolished the ability of CtBP1 to repress the E-cadherin promoter activity. Notably, SUMOylation of CtBP1 was inhibited by the PDZ domain of nNOS, correlating with the known inhibitory effect of nNOS on the nuclear accumulation of CtBP1. This study identifies SUMOylation as a regulatory mechanism underlying CtBP1-dependent transcriptional repression.